In vitro Antifungal Activities of Extracts of Fruits and other Morphological Parts of Xanthium strumarium Against the Plant Pathogen, Rhizoctonia solani: Rhizoctonia solani Control by Plant Extract - Osman, Nour Ahmed; Alsiddeeg, Samia Elias; Ahmed, Nafeesa Elmahi; Ali Elhussein, Salah Ahmed (Biological Sciences - PJSIR, 2014)